POTENSI EKOLOGIS HASIL HUTAN BUKAN KAYU (HHBK) DALAM MENOPANG ASPEK SOSIAL EKONOMI DAN BUDAYA MASYARAKAT PEGUNUNGAN: KASUS DESA HUKUANAKOTA KABUPATEN SERAM BAGIAN BARAT - Pietersz, Juglans Howard; Wattimena, Cornelia M. (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
The research aims to assess the potential of Non-Timber Forest Products (NTFPs) and their carrying capacity for supporting the social and economic aspects of the Hukuanakota Village community. The study uses a survey and descriptive method, with interviews conducted via questionnaires. Vegetation analysis reveals Damar as the dominant species in terms of land area, with the highest Importance Value Index (INP = 117.979%), Lasa wood (INP= 67,699 %), Cempedak (INP =25.950%), Cengkeh (INP = 19.578%), and Durian (INP = 15.134%). NTFPs have proven to provide strong support in economic, social, and cultural aspects for the people of Hukuanakota. However, NTFP management remains traditional. The community faces several challenges, including limited market access, complex marketing permit processes for NTFPs, and the draw of local human resources toward better livelihood opportunities outside the village.